European Dimension of the Constitution of Finland - Gawłowicz, Izabela (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Facing the wonderful challenge that Professor Andrzej Bisztyga put me through, I will examine the sings of European-ness in the constitution of Finland - strongly Nordic, highly developed and human rights - oriented state with the knowledge-based cyber society. The main aims of this article are twofold. First, the aim is to examine the provisions of the Constitution of Finland from the perspective called widely "European", that can be understood as just "regional", but seen from the point, where it means "common" and "built on long and rich legal tradition".
Keywords: wartości europejskie; aksjologia europejska; konstytucja; wymiar europejski; prawa człowieka; wartości Unii Europejskiej; europeizacja; Finlandia - konstytucje; constitution; Constitution of Finland; EU values; Europeization; European axiology; European dimension of constitution; European spirit; human rights